Ideological Apologetics of the Communist Party in Suppressing National Resistance (1944–1953) - Bagušauskas , Juozapas Romualdas (Genocidas ir rezistencija, 2004)
After the Second World War, Lithuania suffered one of the most terrible periods in the country's history. Repressive structures were dominant. The restored party and government institutions tolerated this situation, because they considered the growing national resistance movement a threat to their very existence. The activities of Lithuanian Communist organisations were controlled by the VKP(b) (All-Union Communist (Bolshevik) Party) CC (Central Committee), which approved decisions intended to sovietise the country and destroy the spiritual life of the nation. A special Lithuanian bureau of the VKP(b) CC directly controlled the activities of Lithuanian Communists and issued directives in their name.
Keywords: communist party; armed resistance; communist propaganda